Economic Growth, Poverty Gap, and Health Inequality: Implications Based on Panel Analysis of Organization for Economic Cooperation and Development Data - Han, Sangik (UI Scholars Hub, 2024)
This study investigated the impact of economic growth and income distribution on health inequality using data from the Organization for Economic Cooperation and Development (OECD). Employing a panel analysis, this study amalgamated 21 years of data (spanning from 2000 to 2020) from 37 OECD countries. The dependent variables (life expectancy and avoidable mortality) were scrutinized against independent variables (gross domestic product and poverty gap). Control variables encompassed body mass index, consumption patterns, smoking rates, health workers availability, number of beds in health facilities, national medical expenses, and unemployment rates. This study revealed significant associations between economic growth, poverty gap, and both life expectancy and avoidable mortality. This underscored the necessity of prioritizing not only income distribution but also overall economic growth to address health inequality effectively. This study established that an increase in the poverty gap corresponded to elevated life expectancy and reduced avoidable mortality rates, suggesting a mechanism distinct from a medical security system targeting lower-income individuals or an enhancement of societal welfare. Proposing policy measures to alleviate health inequality, this study advocates for policy interventions to mitigate the adverse impacts of income inequality within healthcare policies.